Evidence That the Etiology of Congenital Hypopituitarism Has a Major Genetic Component but Is Infrequently Monogenic - Jee, Youn Hee; Gangat, Mariam; Yeliosof, Olga; Temnycky, Adrian G.; Vanapruks, Selena; Whalen, Philip; Gourgari, Evgenia; Bleach, Cortney; Yu, Christine H.; Marshall, Ian; Yanovski, Jack A.; Link, Kathleen; et al. (Frontiers in Genetics, 2021)
Purpose: Congenital hypopituitarism usually occurs sporadically. In most patients, the etiology remains unknown. Methods: We studied 13 children with sporadic congenital hypopituitarism. Children with non-endocrine, non-familial idiopathic short stature (NFSS) (n=19) served as a control group. Exome sequencing was performed in probands and both unaffected parents. A burden testing approach was used to compare the number of candidate variants in the two groups. Results: First, we assessed the frequency of rare, predicted-pathogenic variants in 42 genes previously reported to be associated with pituitary gland development. The average number of variants per individual was greater in probands with congenital hypopituitarism than those with NFSS (1.1 vs 0.21, mean variants/proband, P = 0.03). The number of probands with at least 1 variant in a pituitary-associated gene was greater in congenital hypopituitarism than in NFSS (62% vs 21%, P = 0.03). Second, we assessed the frequency of rare, predicted-pathogenic variants in the exome (to capture undiscovered causes) that were inherited in a fashion that could explain the sporadic occurrence of the proband’s condition with a monogenic etiology (de novo mutation, autosomal recessive, or X-linked recessive) with complete penetrance. There were fewer monogenic candidates in the probands with congenital hypopituitarism than those with NFSS (1.3 vs 2.5 candidate variants/proband, P = 0.024). We did not find any candidate variants (0 of 13 probands) in genes previously reported to explain the phenotype in congenital hypopituitarism, unlike NFSS (8 of 19 probands, P = 0.01). Conclusion: Our findings provide evidence that the etiology of sporadic congenital hypopituitarism has a major genetic component but may be infrequently monogenic with full penetrance, suggesting a more complex etiology.